An Overview on Self - Concept of Teenagers: Exploring the Impact of Self-Concept on Teenagers' Mental Health (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Children are a very important factor in the world today. At the same time, adolescents are at the center. Because this is the future of the whole world and it is a big responsibility to take care of these adolescents and their holistic development. Children and adolescents have always been an important focus of study for mental health researchers. Studies have highlighted emotional problems such as depression, anxiety, and difficulties in social interaction as well as behavioral problems such as hyperactivity and conduct problems in them.